EMERGING ANTIBIOTIC RESISTANCE IN OPPORTUNISTIC BACTERIA FROM TRACHEAL ASPIRATES OF INTENSIVE CARE SARS-COV-2 PATIENTS - Santos, Maria da Silva; João , Luiz Pereira de Souza; Rodrigues, Ana Carolina dos Santos (American Research Journal of Nursing and Health Sciences (ARJNHS), 2023)
The emergence and rapid spread of the Coronavirus (SARS-CoV-2) in 2019 led to a global pandemic, impacting public health systems worldwide. This novel virus presented a wide spectrum of symptoms, ranging from mild respiratory distress to severe cases resulting in fatalities due to lung failure. In this context, Brazil faced a significant challenge as the virus infiltrated its borders, with the first confirmed case reported in February 2020. This paper sheds light on the situation in the state of Santa Catarina, Brazil, with a particular focus on the city of Lages, offering insights into the pandemic's impact and the healthcare system's response. By October 2021, Santa Catarina had witnessed 1,200,905 confirmed COVID-19 cases, with a notable recovery rate of 97.83%, yet a concerning case fatality rate of 1.62%. The city of Lages, situated in this state, reported 28,614 confirmed cases, with 529 unfortunate fatalities. This study unfolds against the backdrop of the pandemic's chaos in this region, characterized by temporary closures of public places and non-essential businesses. Furthermore, the initial phases of vaccination were limited to healthcare workers and high-risk groups, contributing to a challenging environment. One of the notable consequences of this situation was the overwhelming demand for intensive care unit (ICU) beds and hospitalization. Patients often had to endure long waits at screening facilities, where resources were limited. Alternatively, they were transferred to hospitals in neighboring towns and cities as per bed availability. To address this crisis, a pivotal step was taken by one of the hospitals in Lages, which opened additional ICU wards. These five dedicated ICU wards played a crucial role in offering specialized and tailored care to COVID-19 patients, contributing significantly to the region's healthcare capacity. This study serves as a case study that delves into the dynamics of the pandemic in Lages, Santa Catarina. It examines the challenges faced by the healthcare system and the critical role played by the newly established ICU wards in patient management. Moreover, it underscores the importance of a flexible and adaptive healthcare infrastructure in times of public health emergencies. Understanding the experiences and lessons from this region can provide valuable insights for policymakers and healthcare professionals globally, as they navigate and prepare for future challenges posed by infectious diseases